The Effect of Private-Debt-Underwriting Reputation on Bank Public-Debt Underwriting - Narayanan, Rajesh P.; Rangan, Kasturi P.; Rangan, Nanda K. (Review of Financial Studies, 2007)
We provide evidence that commercial banks extend their reputation in underwriting syndicated loans and private placements (private debt) to their bond-underwriting activities. In the absence of bond market reputation, private-debt-market reputation enables commercial banks to win underwriting mandates from their loan clients. Furthermore, it allows them to credibly commit to investors against opportunistically using lending information and thereby deliver superior certification benefits in the form of higher issue prices relative to investment-bank underwriters. This pricing benefit is not offset by higher underwriting fees and thus results in lower total issuance costs for borrowers.